Virtual methods in object paradigm - Janusz, Robert (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2007)
The role of virtual methods in object oriented programming is presented. The object oriented approach is extended to the philosophical domain of rational thinking and virtual methods are used as a link between scientific and philosophical domains.